Gastroprotective and Anti-Helicobacter Pylori Potentials of Pistacia atlantica Gum Essential Oil Using Experimental Rat Models: Pistacia atlantica gum essential oil and peptic ulcer - Khoramjouy, Mona; Feizi, Afsoon; Qaderi, Adel; Bahari, Delnia; Khezrian, Somayeh; Gholamine, Babak; Kobarfard, Farzad; Naseri, Veria; Faizi, Mehrdad (Iranian Journal of Pharmaceutical Sciences, 2025)
Gastric ulcers are one of the disorders that have a substantial effect on people’s lives, and many treatment options come with side effects. This study was conducted to explore the protective and therapeutic properties of the essential oil of the Pistacia atlantica subspecies kurdica gum on gastric ulcers and gastropathy in rats and its acute oral toxicity and chemical analysis. The animals were administered the essential oil at different doses (12.5, 25, 50, and 100 mg/kg of body weight orally for 21 days) before receiving 85% ethanol. The stomachs were then removed for macroscopic and microscopic examination. Then, we used the Helicobacter pylori-induced rat model of gastropathy. The oral administration of the essential oil at doses of 12.5, 25, 50, and 100 mg/kg of body weight showed strong dose-dependent protection against stomach ulcers caused by ethanol, Additionally, the histological examination shows that the essential oil can prevent ethanol-caused stomach ulcers. Administration of the gum at a dose of 100 mg/kg for 21 days may have antibacterial effects on H. pylori. The findings showed that the essential oil of Pistacia atlantica gum, which contains a high quantity of alpha-pinene (>90%), can be beneficial in treating and preventing peptic ulcers in rat models caused by ethanol and H. pylori.